Research and design of smart campus for digital twins - LI Luying; CHEN Ping; WANG Xingjian; LI Chunxiao (Tongxin xuebao)
With the acceleration of digital transformation in education, digital twin technology provides new perspectives and methods for the development of smart campuses. The development prospects of digital twin technology and its current applications within the education sector were comprehensively reviewed, along with its potential contributions to the construction of smart campuses. The conceptual connotation and application characteristics of digital twin smart campuses were clarified, and a logical model oriented towards digital twins was proposed. The technical architecture, characterized as “six horizontal and three vertical” was further refined, and an in-depth discussion of the key technologies necessary to implement this architecture was provided. A three-stage evolution path for the development of digital twin smart campuses was also outlined. This framework aims to offer theoretical support and practical guidance for smart campus planning and implementation, thereby empowering the construction of high-quality educational campuses in the field of education.